2009
DOI: 10.1557/jmr.2009.0327
|View full text |Cite
|
Sign up to set email alerts
|

Rapid synthesis of bulk Ti2AlC by self-propagating high temperature combustion synthesis with a pseudo–hot isostatic pressing process

Abstract: In this study, the dense polycrystalline Ti2AlC was synthesized by self-propagating high-temperature combustion synthesis with the pseudo–hot isostatic pressing process (SHS/PHIP). The resultant phase purity is highly dependent on the mol ratio of raw powders. The Ti2AlC was densified by applying pressure after the SHS reaction. The resultant sample mainly contains typical plate-like nonstoichiometric Ti2AlCx (x = 0.69) with grain size of ∼6 µm. The sample shows the Vickers hardness of 5.5 GPa, highest flexura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 20 publications
7
63
2
2
Order By: Relevance
“…The experimental details can be found elsewhere [16]. By using the Rietveld method [17], phase quantification analysis confirmed that TiC concentration was 5% in volume. Samples were cut into rectangular bars with a dimension of 3 × 4 × 30 mm 3 from the central part of the bulk materials by the electrical discharge machining method.…”
Section: Methodsmentioning
confidence: 95%
“…The experimental details can be found elsewhere [16]. By using the Rietveld method [17], phase quantification analysis confirmed that TiC concentration was 5% in volume. Samples were cut into rectangular bars with a dimension of 3 × 4 × 30 mm 3 from the central part of the bulk materials by the electrical discharge machining method.…”
Section: Methodsmentioning
confidence: 95%
“…Recent work in the literature suggests that Ti 2 AlC exists over a range of stoichiometries. For example, Bai et al recently reported the existence of a Ti 2 AlC x phase where x was as low as 0.69 [53,54]. Herein, it is more likely than not that the Ti 2 AlC is Al-deficient since it is believed that the loss of Al is what triggers the transformation to the 523 and possibly the 312 phase.…”
Section: A Lattice Parameters Expansions and Anisotropiesmentioning
confidence: 99%
“…With regard to the Ti 2 AlC MAX-phase material, the majority of research conducted to date is based on dense material [9,10,15,[24][25][26][27][28]. Hu et al [18] and Zhou et al [20] reported the production of porous Ti 2 AlC and Ti 3 SiC 2 respectively, prepared using NaCl as the pore former for controlling the volume fraction of porosity and the pore size.…”
Section: Introductionmentioning
confidence: 99%